Study on influence of dense medium on impact pressure of detonation waves subjected to contact blasts - MENG Yuanpei; MA Yue; HE Yuan; GUO Lei; LING Qi; ZHOU Jie; WANG Chuanting; HE Yong (Xibei Gongye Daxue Xuebao)
In order to investigate the buffering effect of the different dense medium on the shock waves in the contact blasts, a dimensional analysis method by using the zero-pressure sound speed of dense medium was proposed. The present approach led to the establishment of a dimensionless relationship describing the influence of the impedance on the vertical incident pressure. To validate this methodology, the classical detonation wave propagation theory was employed to calculate the pressure values of shock waves propagating into typical dense medium. Additionally, finite element analysis software was used to simulate the initiation processes of three types of explosives with different dense medium acting as buffer layers. Explicit simulations accurately reproduced the reflection of shock waves/rarefaction waves within the explosives after passing through medium with varying impedances, with the error in pressure value calculations being controlled below 8%. Combining these results with the assumptions made in dimensional analysis and a large dataset, the specific form of the dimensionless relationship was established. Subsequently, a dimensionless model for pressure of shock waves incident on dense medium, based on the explosive density and detonation velocity, was developed. By comparing the predicted with the experimental results, it was found that the error was below 10%, thus confirming the accuracy of the model in engineering applications. Moreover, since obtaining the zero-pressure sound impedance is much easier than that by using the Hugoniot relation, the present model greatly simplifies the computational complexity and provides the useful references for predicting the pressure values incident on novel dense medium.